Self-defective ZnS mediated charge transfer for bran-new inter-step mode with boosted photoactivity and enhanced photostability. (6th January 2021) - Wang, Fang; Le, Shukun; Song, Fanyue; Su, Yiguo
Abstract: The appropriate interfacial contact and charges transfer mode of heterojunction photocatalysts were critical for high-efficiency hydrogen production. Inter-step mode heterojunction composite had advantages of enhanced visible-light response, improved charge space separation rate, increased electron utilization, which could also protect catalyst anode from photocorrosion. Zinc-vacancy-rich ZnS decorated CdS heterojunction photocatalyst with inter-step mode was constructed in order to fundamentally enhance photocatalytic performance and overcome photocorrosion of CdS. The charge transfer mode was modulated from pervasive type-II to bran-new inter-step mode by defect engineering. Zinc vacancies functioned as acceptor level for charge separation and up-shifted conduction and valance band energy of ZnS. The defective engineered CdS/ZnS heterojunction displayed a reduced over-potential and enhanced photocatalytic activity. The optimal photocatalytic hydrogen production rate for CdS/ZnS reached 42.1 mmolg −1 under visible light without any co-catalyst. An apparent quantum yield (AQY) of 38.75% at 450 nm was achieved, which was 269.3 and 71.9 times higher than pristine zinc-vacancy-rich ZnS and CdS, respectively. Meanwhile, holes aggregated on the surface of CdS were blocked and the oxidation corrosion process was suppressed. The charge transfer mechanism and kinetics of charge transfer and separation in inter-step mode heterojunction photocatalysts were investigated and discussed. This work will accelerate practical applications of photocatalysis with inter-step mode and give deep insights into understanding how inherent acceptor levels play a role in designing defect-engineered semiconductor with enhanced photocatalytic performance. Graphical abstract: A nano-heterojunction photocatalyst ZnS/CdS was constructed by modulating charge transfer to show inter-step mode with incorporation of Zn-defective engineering. The interface electron transfer depended on electronic band potentials and internal electric field in bran-new inter-step mode. Image 1 Highlights: Zinc-vacancy ZnS/CdS inter-step mode photocatalyst was constructed for boosting H2 evolution. The stability of zinc-vacancy ZnS/CdS photocatalystis obviously improved in comparison to CdS. Mechanism of charge transfer and separation in inter-step mode heterojunction was discussed.